Water Balance Analysis Using the NRECA Method and the FJ Mock Method with the WEAP (Water Evaluation and Planning) Application in the Way Pisang Watershed - Devi Peggy Utami; Any Nurhasanah; Sugito Sugito; Aprizal Aprizal (Lembaga Pengembangan Kinerja Dosen, 2026)
In a watershed, discharge data is essential to determine the flow rate of a river and is used to meet the daily water requirements of humans, plants, and animals. The Way Pisang watershed is a part of the Way Sekampung watershed, administratively located in the South Lampung Regency. In this study, the water demands analyzed include domestic, livestock, irrigation, and industrial needs. These water demands are compared with the water availability in the Way Pisang watershed. The analysis of water availability was conducted using the NRECA and FJ Mock methods, yielding results of 68.75 m³/s and 59.88 m³/s, respectively. Meanwhile, the water balance calculation was performed using the NRECA and FJ Mock methods through WEAP software. The results indicate that from January to November, the Way Pisang watershed experiences a surplus level of 63% (NRECA method), 57.7% (FJ Mock method), and 63.4% (WEAP method). Conversely, in December, it faces a deficit level of 0.62% (NRECA method), 1.37% (FJ Mock method), and 0.72% (WEAP software).